2015
DOI: 10.1590/0074-02760140276
|View full text |Cite
|
Sign up to set email alerts
|

The use of halloysite clay and carboxyl-functionalised multi-walled carbon nanotubes for recombinant LipL32 antigen delivery enhanced the IgG response

Abstract: We studied the feasibility of using halloysite clay nanotubes (HNTs) and carboxyl-functionalised multi-walled carbon nanotubes (COOH-MWCNTs) as antigen carriers to improve immune responses against a recombinant LipL32 protein (rLipL32). Immunisation using the HNTs or COOH-MWCNTs significantly increased the rLipL32-specific IgG antibody titres (p < 0.05) of Golden Syrian hamsters. None of the vaccines tested conferred protection against a challenge using a virulent Leptospira interrogans strain. These results d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…Additionally, several studies have shown that functionalised CNTs do not cause cytotoxic effects (10,11,28,29) as observed in this work. Amino-functionalised NPs were found to interact with negatively charged DNA and the cell membrane, and through this interaction, these successfully delivered the pTARGET/lemA plasmid into mammalian cells without any cytotoxicity.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Additionally, several studies have shown that functionalised CNTs do not cause cytotoxic effects (10,11,28,29) as observed in this work. Amino-functionalised NPs were found to interact with negatively charged DNA and the cell membrane, and through this interaction, these successfully delivered the pTARGET/lemA plasmid into mammalian cells without any cytotoxicity.…”
Section: Discussionsupporting
confidence: 79%
“…Freund's adjuvant, (7) aluminum hydroxide, (5) Ad-daVax ™ , (6) CpG oligodeoxynucleotides (or CpG ODN), xanthan gum, (8) mannosylated form, (9) and NPs. (10,11) NPs seemed to be potential antigen carriers for the development of new-generation vaccines, and combined nanovaccines have been known to induce more intense and long-lasting antigen-specific immune responses. NPs can induce a robust innate immunity response by causing abundant initial antigen exposure and long-term immunity through the sustained release of antigens via two types of activation modes: dendritic cell (DC) and T-cell differentiation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Immunisation with a surface protein of Anaplasma marginale , rMSP1a, associated with MWCNTs, significantly induced high levels of anti-MSP1a IgG (Silvestre et al 2014). Recently, the association of halloysite and COOH-MWCNTs with LipL32 antigen from L. interrogans was shown to enhance IgG response at higher levels than that obtained through Alhydrogel; however, none of the animals were protected against challenge (Hartwig et al 2015). …”
mentioning
confidence: 99%
“…Immunization using the HNTs and COOH-MWCNTs increased to a remarkable extent the rLipL32-specific IgG antibody titres of golden Syrian hamsters with leptospirosis disease (Hartwig et al, 2015). Gene therapy is facing problems with use of viral vectors; in recent years, therefore, new non-viral gene carriers have attracted much attention.…”
Section: H N Ts U S E D I N T H E D E L I V E Ry O F Vac C I N E S a mentioning
confidence: 99%